A Comparative Study of Ten Pear (Pyrus communis L.) Cultivars in Relation to the Content of Sugars, Organic Acids, and Polyphenol Compounds - Asima Akagić; Amila Oras; Fuad Gaši; Mekjell Meland; Pakeza Drkenda; Senad Memić; Nermina Spaho; Sanja Oručević Žuljević; Igor Jerković; Osman Musić; Metka Hudina (Foods, 2022)
Traditional pear cultivars are increasingly in demand by consumers because of their excellent taste, the possibility of use in sustainable food production systems, convenience as raw materials for obtaining products of high nutritional quality, and perceived health benefits. In this study, individual sugars, organic acids, and polyphenols in the fruits of nine traditional and one commercial pear cultivar during two growing seasons were determined by HPLC. A significant influence of cultivars, growing years, and their interaction on the content of analyzed primary and secondary metabolites was determined. The commercial pear cultivar ‘Président Drouard’ and traditional cultivars ‘Dolokrahan’, ‘Budaljača’, and ‘Krakača’ had a lower content of all analyzed sugars. Overall, traditional pear cultivars had higher total polyphenols in the peel and pulp than ‘Président Drouard’, with the exception ‘Takiša’ and ‘Ahmetova’. High polyphenol content detected in ‘Budaljača’, ‘Dolokrahan’, and ‘Krakača’ shows the utilization value of traditional pear germplasm. The obtained data can serve as practical supporting data for the use of traditional pears in the neutraceutical, pharmaceutical, and food industries.